(untitled) (Research, Society and Development, 2022)
The expansion of agribusiness has led to the expropriation of rural people, making them, many times, give up acquired rights with a lot of struggle. Among these rights, we can highlight the Education of the Country, which only reached the rural environment in the late 20th century. This study aims to understand and understand the opinion of young people from rural areas about agribusiness and its environmental and social implications, as well as about the importance of the permanence of small family farmers in the countryside. The research was carried out at the Sol Nascente State School, in the city of Confresa/MT. This country school serves from Kindergarten to High School and also Youth and Adult Education (EJA). However, for data purposes, the research emphasized only high school seniors, seeking their concept and knowledge regarding the arrival of agribusiness in the region. Seven students from the 3rd year of high school participated in the research. A questionnaire consisting of 6 questions was used as a data collection instrument. With the results obtained, it was possible to perceive that the vision of young people, in relation to the expansion of agribusiness, is still understood as something positive that values ​​properties in the region and boosts the economy. They do not see it as the cause of man’s departure from the countryside, however, they understand the environmental effects and impacts caused by the expansion of agribusiness.